A Review of the Role of Serotonin, TIMP-1, and CXCL-1 in the Diagnosis and Differentiation of Irritable Bowel Syndrome - Duaa Radhi Aladhab et al. (International Journal of Scientific Research and Innovative Studies, 2025)
Irritable Bowel Syndrome (IBS) is a common functional gastrointestinal disorder characterized by chronic abdominal pain and altered bowel habits, with a complex, multifactorial pathophysiology. Current diagnosis relies on symptom-based Rome IV criteria, lacking reliable biomarkers for objective diagnosis and subclassification (IBS-C, IBS-D, IBS-M). Emerging research highlights the potential roles of serotonin (5-HT), Tissue Inhibitor of Metalloproteinase-1 (TIMP-1), and Chemokine (C-X-C Motif) Ligand 1 (CXCL-1) in IBS pathophysiology. This narrative review critically evaluates the evidence for serotonin, TIMP-1, and CXCL-1 as potential biomarkers for diagnosing IBS and differentiating its subtypes. A synthesis of contemporary literature from peer-reviewed journals, focusing on human studies, meta-analyses, and clinical trials from the past 15 years, was conducted. Key Findings: (1) Serotonin: Dysregulation of the enteric serotonergic system is well-established in IBS. Elevated postprandial plasma 5-HT and increased mucosal 5-HT signaling are more pronounced in IBS-D, while reduced 5-HT reuptake (via SERT) is common. Platelet-depleted plasma 5-HT shows promise as a differential biomarker. (2) TIMP-1: As an inhibitor of matrix metalloproteinases (MMPs), elevated serum and colonic TIMP-1 levels are associated with low-grade mucosal immune activation and altered intestinal permeability, particularly in post-infectious IBS (PI-IBS) and IBS-D. The TIMP-1/MMP ratio may reflect a dysregulated tissue repair process. (3) CXCL-1: This pro-inflammatory chemokine is elevated in the serum and colonic mucosa of IBS patients, correlating with pain severity and neutrophil recruitment. Levels are highest in IBS-D and PI-IBS, suggesting its role in sustained, subclinical inflammation and visceral hypersensitivity. While none are yet diagnostic alone, serotonin, TIMP-1, and CXCL-1 represent promising biomarker panels that reflect key IBS pathophysiological pillars: neurotransmitter dysregulation (5-HT), impaired barrier function and remodeling (TIMP-1), and neuroimmune activation (CXCL-1). A multi-biomarker approach, potentially combining these with other markers, could move IBS diagnosis beyond symptom criteria, enable mechanistic subclassification, and guide targeted therapies. Keywords: Irritable Bowel Syndrome, Biomarkers, Serotonin, 5-HT, TIMP-1, CXCL-1, Diagnosis, IBS Subtypes. Received Date: October 20, 2025 Accepted Date: November 11, 2025 Published Date: December 01, 2025 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/540